Faktor-Faktor Yang Berhubungan Dengan Siklus Menstruasi Pada Remaja Putri Kelas XI di SMAN 3 Cikarang Utara Kabupaten Bekasi Tahun 2019 - Ade Krisna Ginting; Ikha Prastiwi; Marini Iskandar (UP3M AKPER-AKBID BHAKTI HUSADA CIKARANG, 2020)
Background :Based on Yudhya Erry's research in 2016 in Jakarta, the majority of respondentsfound that 68.7% of respondents experienced abnormal menstrual cycles with thin nutritionalstatus and irregular menstrual cycles. Factors affecting the menstrual cycle include menarche,being overweight and underweight and excessive physical activity. The existence of hormonaldisorders in women namely progesterone, estrogen, LH, and FSH are related to nutritionalstatus. Nutritional status has an important role in the menstrual cycle.Method :This study uses analytical research methods with cross-sectional design, with thevariables studied consist of the dependent variable, namely: the menstrual cycle and independent variables, namely: Menarche, BMI and physical activity. The sampling technique is totalsampling. With a population of 97 XI class XI students in SMAN 3 Cikarang Utara.Result: Based on the results of the Chi Square analysis p value = 0.003, because p <0.05, it canbe concluded that there is a relationship between BMI and the menstrual cycle. Odds Ratio (OR)= 0.251. There is no relationship between menarche and physical activity with the cycle ofteenage girls.It is recommended that young women maintain their nutritional adequacy and schoolsshould improve education about reproductive health issues, especially for young women,especially related to nutritional needs of adolescents by holding counseling and putting upposters, leaflets, and bulletin on the importance of maintaining adequate nutrition in adolescentsand their impact on reproductive health .